Peritoneal Dialysis Fluid‐Induced Fragmentation of Golgi Apparatus as a Biocompatibility Marker. Issue 6 (23rd February 2018) - Iwamoto, Masanao; Okazaki, Alice; Murata, Sayaka; Hirukawa, Masaki; Miyamoto, Keiichi; Murata, Tomohiro; Ishikawa, Eiji; Yoshida, Toshimichi; Horiuchi, Takashi
Abstract: In vitro biocompatibility assessments that consider physiologically appropriate conditions of cell exposure to peritoneal dialysis fluids (PDFs) are still awaited. In this study, we found that fragmentation of Golgi apparatus occurred in a pH‐dependent manner within 30‐min exposure to five distinct commercially available PDFs, which showed no marked difference in their effects on cell viability in the conventional MTT assay. Fluorescence microscopy analysis of labeling antibody against cis‐Golgi protein GM130 indicated that the stacked cisternal structure was maintained in the perinuclear area of both M199 culture medium and a neutral‐pH PDF groups. However, this specific structure became partially disassembled over time even in a neutral‐pH PDF, and fragmentation was markedly enhanced in cells exposed to neutralized‐pH PDFs in correspondence with their intracellular pH; moreover, in acidic PDFs, Golgi staining was diffuse and scattered in the entire cytoplasm and showed partial aggregation. The Golgi fragmentation markedly observed with the neutralized PDFs could be reversed by replacing either the media with a neutral‐pH medium or a mixture of PDF and PD effluent (PDF) in a gradient manner mimicking clinical conditions. Furthermore, although weaker than pH effect, notable effects of other PDF‐related factors were also observed after 30‐min exposure to pH‐adjusted PDFs. Lastly, the results of studies conducted using MAPK/SAPK inhibitors indicated that the mechanism underlying the Golgi fragmentation described here differs from that associated with the fragmentation that occurs at the G2/M checkpoint in the cell cycle. We conclude that Golgi fragmentation is suitable for rapid biocompatibility assessment of PDF not only because of its strong pH dependence but also because the fragmentation is recognizably affected by PDF constituents.